2022
DOI: 10.14710/mkmi.21.6.363-373
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Perilaku Merokok Tenaga Kesehatan di Puskesmas Kaliwiro Kabupaten Wonosobo Tahun 2021

Abstract: Latar belakang: Rokok mengandung racun dan zat karsinogenik yang dapat menimbulkan berbagai penyakit hingga kematian. Tenaga kesehatan sebagai promotor kesehatan memiliki peran penting dalam pemberi edukasi pencegahan perilaku merokok serta panutan di masyarakat dengan tidak mengonsumsi rokok. Namun, banyak ditemukan tenaga kesehatan yang menjadi perokok. Hal tersebut dapat memengaruhi keyakinan masyarakat sehingga masyarakat enggan untuk berhenti merokok karena peran yang dijalankan tenaga kesehatan sebagai r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…Based on research (Ulinuha et al, 2022) From the point of view of health workers, they do not agree regarding cigarette advertisements that are shown on television or social media, it is feared that it can influence people's smoking behavior because it can be seen by all groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on research (Ulinuha et al, 2022) From the point of view of health workers, they do not agree regarding cigarette advertisements that are shown on television or social media, it is feared that it can influence people's smoking behavior because it can be seen by all groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, many health workers are found to be smokers. Knowledge about the dangers of smoking should be owned by health workers but they are ignored by continuing to consume cigarettes and then there is an argument that smoking can calm the mind and various other reasons which can be called educational distortions (Ulinuha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Bakteri S. epidermidismenjadi agen penting penyebab terjadinya infeksi nosokomial (Nugraheni dan Winarni, 2012)…”
Section: Aureusadalah Methicillin Resistant Staphylococcus Aureus(mrsa)unclassified
“…Smokers are also more likely to quit smoking when they receive counseling from health workers ( 9 ). Unfortunately, there are still health workers who are active smokers, so this condition contributes to the prevalence rate of smokers and hinders smoking cessation programs in Indonesia ( 10 , 11 ). Health workers who should be role models for the community not to smoke and live a healthy life are still consuming cigarettes ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still many smoking health workers in the area. Some health workers on the island of Java smoke because they are tired after work ( 11 ). Study in Grobogan, Central Java found that 35% of health service employee were smoked ( 18 ), likewise it was found that 36% of health workers aged 31–40 in Bali ( 10 ).…”
Section: Introductionmentioning
confidence: 99%